GOVERNMENT ACCOUNTING STANDARDS AND INTERNAL CONTROL SYSTEM ON THE QUALITY OF LOCAL GOVERNMENT FINANCIAL REPORTS - Abdul Hafiz Tanjung; Dewi Nurhasanah (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2023)
This study aims to determine the application of government accounting standards, internal control systems and the quality of local government financial reports in the Cimahi City government, as well as to test the variables of government accounting standards and internal control systems whether they have influence on the quality of local government financial reports on the Cimahi City government either partially or simultaneously. The population in this study were employees of the Regional Financial and Asset Management Agency (BPKAD) and the Regional Government Inspectorate of Cimahi City with a sample of 45 respondents. Methods of data collection using a questionnaire. The research method used is descriptive and associative methods. The data processing method is the SEM method, namely Pastial Least Squares SEM (PLS-SEM) with the help of SmartPLS 3. The results of the study state that the application of government accounting standards and internal control systems has a significant positive effect on the quality of local government financial reports either partially or simultaneously on the government. Cimahi City.